Evaluation of Reverse Transcription-PCR and a Bacteriophage-Based Assay for Rapid Phenotypic Detection of Rifampin Resistance in Clinical Isolates of Mycobacterium tuberculosis - Eltringham, I. J. (American Society for Microbiology, 1999)
New rapid phenotypic assays for the detection of rifampin resistance in Mycobacterium tuberculosis have recently been described, but most of these require liquid cultures, which reduces the utility of many tests in terms of turnaround times. In the United Kingdom, over 90% of rifampin-resistant isolates are also resistant to isoniazid, so rifampin resistance can be used as a sensitive marker for multidrug-resistant tuberculosis. In this study, two new rapid phenotypic assays were compared to the standard resistance ratio method on 91 clinical isolates of M. tuberculosis. One, the phage amplified biologically (PhaB) assay, has been described previously and is based on the inability of susceptible isolates of M. tuberculosis to support the replication of bacteriophage D29 in the presence of inhibitory doses of rifampin. The other employed reverse transcription (RT)-PCR to demonstrate a reduction in inducible dnaK mRNA levels in susceptible isolates treated with rifampin. After incubation for 18 h with 4 μg of rifampin per ml, the PhaB assay showed concordance with the resistance ratio method for 46 of 46 (100%) susceptible and 31 of 31 (100%) resistant isolates, while RT-PCR showed concordance for 46 of 48 (96%) susceptible and 35 of 36 (97%) resistant isolates. We believe these assays provide a reliable rapid means of susceptibility testing with a total turnaround time of only 48 h, although the PhaB assay is better in terms of its lower technical demand and cost and its applicability to tuberculosis susceptibility testing in developing countries.